Letter of Credit: Saatnya Perdagangan Internasional beralih ke Dokumen Digital dengan eUCP - Zuhri Ruslan (Jurnal Riset Akuntansi dan Keuangan, 2023)
International trade still heavily relies on paper, which is painfully time-consuming. The inefficient process improved by changing the paper documents into digital electronic documents. The research aims to investigate and analyze the electronic Uniform Customs Practice (eUCP) as a legal base for using electronic documents in Letter of Credit (LC) in international trade. The method employed was document analysis and is an explanatory research. The research reveals that document digitalization increases the effectiveness of the LC process. However, the bill of exchange, the bill of lading and certificate of origin cannot be digitalized in current circumstances.